2021
DOI: 10.5267/j.uscm.2020.7.008
|View full text |Cite
|
Sign up to set email alerts
|

Success factors of lean six sigma implementation in manufacturing

Abstract: Recently, Lean Six Sigma (LSS) has attracted much attention from both researchers and practitioners. In fact, many published papers used a quantitative research methodology to build and test theory in the field of LSS implementation in manufacturing area. Very few studies have been reported about the critical success factors influencing of six sigma implementations. The aim of this study is to present the results, from an empirical evidence, of Six Sigma implementation in Tunisian manufacturing. Therefore, fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…The core activity of the lean method in business process management is to identify the value for the customer and to identify the waste of resources, cost and time in the process (Pal et al ., 2014, Ramos et al ., 2018, Singh et al ., 2019, Sreedharan et al ., 2020, Mabrouka et al ., 2021). By identifying waste, the bottlenecks of the process can be resolved by improving the process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The core activity of the lean method in business process management is to identify the value for the customer and to identify the waste of resources, cost and time in the process (Pal et al ., 2014, Ramos et al ., 2018, Singh et al ., 2019, Sreedharan et al ., 2020, Mabrouka et al ., 2021). By identifying waste, the bottlenecks of the process can be resolved by improving the process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…2.2 Identification of the key factors to Lean Six Sigma implementation in manufacturing supply chains LSS implementation factors are complex and abundant (Mabrouka et al, 2021), and some of the reported LSS implementation failures are attributed to a poor understanding of cause and effect relationships between the LSS enablers (Perera et al, 2021). The relationship between LSS factors with the supply chain performance in manufacturing industries has been proven significant (Ahmad et al, 2019;Gultom and Wibisono, 2019;Ali et al, 2020).…”
Section: Lss In the Supply Chainmentioning
confidence: 99%
“…LSS implementation factors are complex and abundant (Mabrouka et al. , 2021), and some of the reported LSS implementation failures are attributed to a poor understanding of cause and effect relationships between the LSS enablers (Perera et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers in business administration and management domain frequently use the intent structure (Sushil, 2012). Establishing a contextual relationship: For n variables, experts are asked n ( n −1) dichotomous questions like whether A leads to B (Mabrouk et al , 2021) in a desired manner (e.g. in “Yes” and “No”).…”
Section: Ism Procedural Aspectsmentioning
confidence: 99%
“…Establishing a contextual relationship: For n variables, experts are asked n ( n −1) dichotomous questions like whether A leads to B (Mabrouk et al , 2021) in a desired manner (e.g. in “Yes” and “No”).…”
Section: Ism Procedural Aspectsmentioning
confidence: 99%